TINGKAT PENGETAHUAN PASIEN PADA PENGGUNAAN OBAT PREKURSOR DI APOTEK SANGIR FARMA KOTA MAKASSAR PROVINSI SULAWESI SELATAN - Amandha Aulia Irawan; tansri, Suhartini (Jurnal Kesehatan Yamasi Makassar, 2023)
Basically, precursors are used officially in the pharmaceutical industry as raw materials for drugs, materials for the manufacture of drug raw materials and basic ingredients in the manufacture of psychotropics and narcotics. This type of research is descriptive observational. Quantitative data was collected by distributing questionnaires to determine the patient's level of knowledge on the use of precursor drugs at Sangir Farma Pharmacy. The population in this study were all patients who came to the Sangir Farma Pharmacy and were willing to fill out a questionnaire. The sample used is respondents who want to get a precursor drug as many as 40 people. The results of this study will obtain the level of patient knowledge on the use of precursor drugs at the Sangir Farma Pharmacy. Research on the level of patient knowledge on the use of precursor drugs at the Sangir Farma Pharmacy shows a fairly good category with a percentage (63.075%).